Evaluation Liver Function Test Abnormalities in Covid-19 Patient in Tertiary Care Hospital, A Cross Sectional Study - Muhammad Kashif Bashir, Umbreen Aslam, Nosheen Zafar, Niamat Ali, Shazia Siddique, (Pakistan Journal of Medical & Health Sciences, 2022)
Since late December 2019, a novel coronavirus illness (COVID-19) outbreak has been detected in Wuhan, China, affecting 215 nations so far. Although respiratory symptoms are the most common symptom in COVID-19 patients, several extra pulmonary organ dysfunctions have also been observed. Previous investigations have found that individuals with COVID-19 had a high incidence of aberrant liver function parameters. The objective of current study will be to evaluate the effect of effects of covid-19 severity on liver function test and hypocalcaemia. Material and Methods: A cross-sectional study conducted at Corona Isolation Wards of Sir Gaga Ram Hospital Lahore from April to June 2019. Total 110 RT PCR Positive Covid-19 patients were enrolled in current study by consecutive sampling technique. The Demographic details, Disease severity, Laboratory Findings of Liver Function Test (LFTs) and outcome of every patient was recorded from on a predesigned proforma. Data was analyzed using SPSS-26. ANOVA was applied to find out the difference between disease severity LFTs level. P-value less than 0.05 considered as significant. Results: The patients' average age was 30.03+15.03. The average length of stay in the hospital was 14.76+2.77 days. There was predominance of Male in current study male [M=60(54.5%) vs. F=50(45.5%)]. There are 48 (43.6%) patients with mild disease, 28 (25.5%) patients with moderate disease, and 34 (30.9%) patients with severe disease. Only 2(1.8%) patients died, while 102(92.7%) patients recovered. The most common symptom experience by patients was Fever, followed by Cough (32), Fatigue (29), Diarrhea (17), sore throat (18). A significant increase was observed in ALT, AST, ALP, Serum Bilirubin, Total Protein, Albumin and Globulin according to disease severity (p-value<0.05) Conclusions: The abnormal liver function test was shown to be more common in moderate to severe cases. The severity of COVID-19 has a major impact on the liver's functional outcome.